Signals for new spin-1 resonances in electroweak gauge boson pair production at the LHC - Alves, A. [UNESP]; Iboli, O. J.P.; Netto, D. Gonçalves; Gonzalez-Garcia, M. C.; Mizukoshi, J. K. (American Physical Society (APS), 2009)
The mechanism of electroweak symmetry breaking (EWSB) will be directly scrutinized soon at the CERN Large Hadron Collider. We analyze the LHC potential to look for new vector bosons associated with the EWSB sector, presenting a possible model independent approach to search for these new spin-1 resonances. We show that the analyses of the processes pp→ℓ+ℓ′-□T, ℓ±jj□T, ℓ′±ℓ+ℓ-□T, ℓ±jj□T, and ℓ+ℓ-jj (with ℓ, ℓ′=e or μ and j=jet) have a large reach at the LHC and can lead to the discovery or exclusion of many EWSB scenarios such as Higgsless models. © 2009 The American Physical Society.